Exploring the genetic variation for sodicity tolerance in Melia dubia evolved in Indian conditions. (11th November 2021) - Kumar, Raj; Banyal, Rakesh; Singh, Awtar; Yadav, Rajender Kumar
Abstract: Soil sodicity is one of the major constraints for the success of afforestation worldwide. High sodicity causes poor soil physical conditions and thus adversely affect tree growth and biomass production. However, considerable intraspecific variation for sodicity tolerance exists in most of the trees species. Presently, no information is available on sodicity tolerance in the genotypes of the industrially important Melia dubia tree. Therefore, we examined twenty‐five genotypes of M. dubia, that has evolved in different parts of India, to elucidate mechanisms and identify traits imparting sodicity tolerance in these genotypes. The experimental evidence showed the significant genetic variability and relationships in genotypes for various morphological and physiological traits in response to the sodicity stress. On an average, sodicity stress reduced plant height, collar diameter, and shoot biomass by 15%, 18%, and 60%, respectively. The shoots Na + concentration had negative correlation with the growth traits. Shoot Na + ions exclusion was found to increase sodicity tolerance and conferred salt tolerance mechanism in M. dubia . Path analysis revealed that the plant height, collar diameter, number of leaves, and branches were major determinants of shoot biomass production. Cluster analysis validated the genotypes response to sodicity and classified the germplasm into sensitive, moderately tolerant, and tolerant category each consisting of nine, eleven, and five genotypes, respectively. Among genotypes, the MDSS06, MDSS13, and MDSS21 produced greater growth and biomass under sodic stress and indicated good growth potential in such soil. The results showed the presence of a high genetic diversity for salt tolerance in Melia, and the identified genotypes can be considered for strengthening the breeding programs aiming at improving the sodicity tolerance of the species. Our result concluded that genetic variation and breeding approaches using the MDSS06, 13, and 21 genotypes have tremendous potential to improve the growth, biomass, and overall productivity of M. dubia under sodic soil conditions.